2023
DOI: 10.3390/pr11113119
|View full text |Cite
|
Sign up to set email alerts
|

Production of High-Porosity Biochar from Rice Husk by the Microwave Pyrolysis Process

Li-An Kuo,
Wen-Tien Tsai,
Ru-Yuan Yang
et al.

Abstract: This study focused on the highly efficient pyrolysis of rice husk (RH) for producing high-porosity biochar at above 450 °C under various microwave output powers (300–1000 W) and residence times (5–15 min). The findings showed that the maximal calorific value (i.e., 19.89 MJ/kg) can be obtained at the mildest microwave conditions of 300 W when holding for 5 min, giving a moderate enhancement factor (117.4%, or the ratio of 19.89 MJ/kg to 16.94 MJ/kg). However, the physical properties (i.e., surface area, pore v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
2
3
1
Order By: Relevance
“…On the other hand, the calorific values of CD-based biochar products were also determined to show their enhancement factors. The findings showed that higher calorific values were obtained under mild microwave conditions, which were consistent with those in a previous study [25]. For example, the The mass yield of CD-based biochar was weighed by the ratio of its residual mass to CD mass fed into the microwave pyrolysis system.…”
Section: Mass Yield and Calorific Value Of Cd-based Biochar Productssupporting
confidence: 90%
See 4 more Smart Citations
“…On the other hand, the calorific values of CD-based biochar products were also determined to show their enhancement factors. The findings showed that higher calorific values were obtained under mild microwave conditions, which were consistent with those in a previous study [25]. For example, the The mass yield of CD-based biochar was weighed by the ratio of its residual mass to CD mass fed into the microwave pyrolysis system.…”
Section: Mass Yield and Calorific Value Of Cd-based Biochar Productssupporting
confidence: 90%
“…For example, the order of the mass yield is given below: 29.85 wt% (BC-DC-300W-10M), 24.37 wt% (BC-DC-440W-5M), 22.03 wt% (BC-DC-440W-10M), and 15.81 wt% (BC-DC-800W-5M). Obviously, the mass yields of CD-based biochar products were lower than those of biochar products from rice husk in a previous study [25], which could be attributed to the different ash contents between CD and rice husk. On the other hand, the calorific values of CD-based biochar products were also determined to show their enhancement factors.…”
Section: Mass Yield and Calorific Value Of Cd-based Biochar Productscontrasting
confidence: 59%
See 3 more Smart Citations